Preferential solvation of 4-carboxyl-2, 6-dinitrophenylazohydroxynaphthalenes in mixed hydroxylic solvents (2021)
Background: The applications of a group of 4-carboxyl-2,6-dintrophenylazohydroxynaphathalenes, AZ-01 to 04, as colourants, chemosensors or synthetic intermediates have been limited by their solubility. Aim: To investigate the effect of solvent mixture composition on the solubility, solution thermodynamics and position of equilibrium processes of the dyes. Method: The UV-visible spectral patterns of the dyes in binary mixtures including Methanol:Water, Ethanol:Water, Methanol:Ethanol, Methanol:Propan-1-ol, Methanol:Propan-2-ol, Propan-1-ol:Water and Propan-2-ol:Water were acquired. The type and quantitative estimation of solute-solvent interactions at play were determined by fitting spectral patterns to solvent parameters using multilinear regression. Results: Preferential solvation was detected by the non-ideality of the plots of E12 as against the mole fractions of cosolvent in all binary mixtures. In pure solvents, the spectral shifts of AZ-01, 03 and 04, which exist predominantly in the hydrazone form, were affected by polarity of solvent milieu while solvent basicity and acidity, in that order, were the significant parameters for AZ-02. In aqueous alcoholic mixtures, solvent polarity was contributory, although to different degrees, to the observed spectral data of the four dyes. However, solvent acidity and basicity were the primary determinants of spectral shifts observed with AZ-04 and AZ-03 respectively. Spectra-structure relationships identified the formation of the charged hydrazone tautomer which requires stabilisation by polar solvent milieu as responsible for the observed trend. In addition, interactions between new aggregated solvent-solvent species and the propionic acid substituent present in AZ-03 contributed to its spectral shifts. Conclusion: The solvatochromic properties of the phenylazonaphthalene series in binary mixtures have been successfully studied.